An exploratory questionnaire survey about overwork on mental health of Japanese elementary and junior high school teachers. Issue 3 (6th May 2021) - Kuwabara, Miki; Oba, Koji; Takano, Nao; Nagamine, Noritoshi; Maruyama, Yoko; Ito, Nobuhiro; Watanabe, Izumi; Ikeda, Chikako; Sakamoto, Junichi
Abstract : Purpose: Occupational stress-relating overwork among teachers predispose to mental disorders and eventually lead to long leave from work. Although some studies have been conducted to assess these problems among elementary and junior high school teachers, a quantitative investigation has been limited to date. In this study, the authors sought to explore the association between overwork and mental stress among Japanese elementary and junior high school teachers. Design/methodology/approach: An exploratory cross-sectional questionnaire survey was carried out on 294 Japanese elementary and junior high school teachers. The respondents filled a questionnaire on personal data, and occupational stress reaction was evaluated by Japanese version of Brief Job Questionnaire. Multiple linear regression model was used to evaluate the association between overwork information and psychological and physical stress. Findings: Working during holidays was significantly likely to increase psychological and physical stress reactions among elementary school teachers (adjusted mean difference = −1.67, 95% CI: −2.81 to −0.54) and junior high school teachers (adjusted mean difference = −5.24, 95% CI: −9.60 to −0.87). A weakly positive association was found between high risk of psychological and physical stress and marital status ( p = 0.005), teacher in charge of class ( p = 0.015) among elementary school teachers. Originality/value: This study indicated an association between working during holidays and psychological and physical stress reactions among elementary and junior high school teachers after adjusting for sociodemographic and work-related status. Further study for the confirmation of this finding is warranted.